Hartz and minds: Happiness effects of reforming an employment agency - Max Deter (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Since the labor market reforms around 2005, known as the Hartz reforms, Germany has experienced declining unemployment rates. However, little is known about the reforms' effect on individual life satisfaction of unemployed workers. This study applies difference-in-difference estimations and finds a decrease in life satisfaction after the reforms that is more pronounced for male unemployed in west Germany. The effect is driven by income and income satisfaction, but not by the unemployment rate. Also unemployed persons who exogenously lost their jobs are affected by the reforms. In line with the structure of the reforms, the effect is stronger on long-term and involuntarily unemployed persons.
Keywords: E24; I31; J64; 330; unemployment; Hartz reforms; happiness; SOEP